2020
DOI: 10.1002/vnl.21799
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of silicone rubber composites reinforced with carbon nanotube, nanographite, their hybrid, and applications for flexible devices

Abstract: New technology is constantly required for updating new generation flexible devices, such as stretchable sensors, flexible electronics, and actuators. In the present study, a stretchable strain sensor, and actuator were developed based on room‐temperature‐vulcanized (RTV) silicone rubber reinforced with carbon nanotubes (CNTs), nanographite (GR), and CNT‐GR hybrids. A CNT‐based strain sensor developed for RTV silicone rubber showed improved stiffness and brittleness. For example, at 5 phr of filler loading, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…In addition, based on these measurements, the GE/SR composites possess good fatigue properties and a higher ability to restore stress. Kumar et al [ 3 , 106 ] also studied the durability of strain sensors for CNT-, CNT-GR-, and CB-based composites. From the results, they found that the resistance loss was negligible, indicating high electromechanical stability for the CNT-, CNT-GR-, and CB-based composites used as strain sensors [ 3 , 106 ].…”
Section: Applicationsmentioning
confidence: 99%
“…In addition, based on these measurements, the GE/SR composites possess good fatigue properties and a higher ability to restore stress. Kumar et al [ 3 , 106 ] also studied the durability of strain sensors for CNT-, CNT-GR-, and CB-based composites. From the results, they found that the resistance loss was negligible, indicating high electromechanical stability for the CNT-, CNT-GR-, and CB-based composites used as strain sensors [ 3 , 106 ].…”
Section: Applicationsmentioning
confidence: 99%
“…Multiwall carbon nanotubes (MWCNTs) have been extensively used in nanocomposites due to their outstanding properties: high Young’s modulus, stiffness, flexibility, and conductivity. Additionally, only a 1% MWCNTs content can lead to an increase of up to 36–42% of the modulus of elasticity for composite material [ 14 , 15 , 16 ]. Even though carbon nanotubes have great potential as nanofillers, a major concern related to the performance of MWCNTs-based nanocomposites is represented by the difficulty of achieving their homogenous dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum disulfide (MoS 2 ) has a special layered structure, similar to graphite, which can enhance the various properties of polymer composites. They can not only improve the mechanical and electrical properties but can also act as a solid lubricant [ 14 , 15 , 16 , 17 ]. The layered structure is connected by a weak van der Waals force between the layers, which has good lubricity, making it possible to form a lubricating film on the surface of the polymer and, therefore, improving the friction and wear performance of the polymer composite [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%